1988
DOI: 10.1084/jem.167.6.1957
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human tumor necrosis factor induces acute reductions in food intake and body weight in mice.

Abstract: We examined the effects of treatment with rHuTNF on food consumption and body weight in C3H/HeJ mice. rHuTNF was administered intraperitoneally either by injections of 3, 12, or 24 micrograms twice a day or by implantation of osmotic pumps that released 0.75, 3, or 12 micrograms per day. Dose-dependent reductions in both food intake and weight were induced by rHuTNF. However, in spite of continued exposure to rHuTNF, the mice developed a resistance to rHuTNF and resumed their pretreatment food intake and weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
53
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(57 citation statements)
references
References 14 publications
4
53
0
Order By: Relevance
“…Similar studies of TNFa or IL-1b, however, have not been reported in infants, either in humans or in animal models. Nonetheless, increases in cytokines and reductions in energy intakes observed in these investigations are consistent with the limited available animal and human studies and other reports associating proinflammatory cytokines to anorectic response to infections (McCarthy et al, 1985;Socher et al, 1988;Michie et al, 1989).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Similar studies of TNFa or IL-1b, however, have not been reported in infants, either in humans or in animal models. Nonetheless, increases in cytokines and reductions in energy intakes observed in these investigations are consistent with the limited available animal and human studies and other reports associating proinflammatory cytokines to anorectic response to infections (McCarthy et al, 1985;Socher et al, 1988;Michie et al, 1989).…”
Section: Discussionsupporting
confidence: 91%
“…These and related observations in human and animal studies (McCarthy et al, 1985;Socher et al, 1988;Michie et al, 1989) also suggest that DHA and EPA supplementation may attenuate anorectic responses to infectious illness.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…There is some evidence from in vivo studies that the potent cytokine TNF 1 (2) is able to induce tolerance-like conditions. For example, pretreatment with TNF in several animal species selectively affects certain TNF effects such as fever, anorexia, and lethality (3)(4)(5) and partially affects gastrointestinal toxicity (6). Cyclooxygenase inhibitors prevent the induction of tolerance to the toxic effect of TNF (7).…”
mentioning
confidence: 99%
“…69(9): 931-937, 2007 Anorexia and weight loss are frequently associated with acute or chronic infections [11,24]. Since several inflammatory cytokines, most notably TNFα and IL-1β, have been shown to induce anorexia and weight loss, it appears to be likely that these cytokines mediate metabolic changes of infection [9,18,23,26,27,35,37]. However, the mechanisms and mediators by which infection induces anorexia are still poorly understood.…”
mentioning
confidence: 99%